The efficacy and safety of Radiofrequency ablation combined with Lenvatinib plus Sintilimab in Unresectable Hepatocellular Carcinoma: a real-world study - Xishu Wang; Ximin Sun; Yongrong Lei; Lingyan Fang; Yuedi Wang; Kai Feng; Feng Xia (BMC Cancer, 2024)
Abstract Background The combination of targeted therapy and immunotherapy has improved the clinical outcomes of unresectable hepatocellular Carcinoma (HCC). However, the overall prognosis remains suboptimal. This study aims to evaluate the efficacy and safety of a novel combination of radiofrequency ablation (RFA) with lenvatinib plus sintilimab in unresectable HCC. Methods In this retrospective study, patients diagnosed with unresectable HCC were included and divided into two cohorts: RFA combined with lenvatinib plus sintilimab (R-L-S group) and lenvatinib plus sintilimab (L-S group). The primary efficacy endpoints were objective response rate (ORR) and progression free survival (PFS). Adverse events were analyzed to assess the safety profiles. Results The median follow-up periods for the entire cohort were 14.0 months. The R-L-S group (n = 60) had a significantly higher ORR than those with L-S alone (n = 62) (40.0% vs. 20.9%; p = 0.022). Moreover, patients in the R-L-S group had improved median PFS (12 vs. 8 months; p = 0.013) and median overall survival (24 vs. 18 months; p = 0.037), as compared with lenvatinib and sintilimab alone. No significant difference in treatment related adverse event (TRAE) of any grade between the two groups. The most common TRAEs of grade ≥ 3 were fatigue 10.0% (6/60) and hand-foot skin reaction 10.0% (6/60) in the R-L-S group and hand-foot skin reaction 11.3% (7/62) in the L-S group. Conclusion In unresectable HCC patients, the incorporation of RFA to lenvatinib plus sintilimab demonstrated improved efficacy without compromising safety compared with lenvatinib plus sintilimab alone.